The Role of Teachers in Handling Behavioral and Discipline Issues of Grade III Elementary School Students - Sagita Avinia Kusuma Dewi; Achmad Fathoni (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the effectiveness of teachers’ roles (both class and subject teachers) in managing the disciplinary behavior of third-grade students in elementary school. The research employed a quantitative approach with an ex post facto correlation design. Data were collected through questionnaires, observations, and documentation, and analyzed using assumption tests, correlation analysis, and multiple regression. Participants included third-grade students, class teachers, and subject teachers, selected through total and purposive sampling techniques. The results indicate that both class and subject teachers significantly contribute to the effectiveness of managing student discipline, with significance values of 0.047 and 0.049 (0.05), respectively. These findings suggest that student discipline is not solely determined by school rules but is also strongly influenced by teachers’ consistency in guiding, supervising, and modeling expected behaviors. Overall, teacher involvement plays a crucial role in enhancing student disciplinary behavior.